2011
DOI: 10.1177/0885328211424623
|View full text |Cite
|
Sign up to set email alerts
|

Bone substitute materials delivering zoledronic acid: Physicochemical characterization, drug load, and release properties

Abstract: Calcium phosphate-like bone substitute materials have a long history of successful orthopedic applications such as bone void filling and augmentation. Based on the clinical indications, these materials may be loaded with active agents by adsorption offering a perspective for providing innovative drug-delivery systems. The highly effective bisphosphonate zoledronic acid (ZOL) demonstrated a strong affinity to biominerals and is known to significantly reduce osteoclastic activity. Support of early bone formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…These opposing results may be attributed to different inorganic phases and bisphosphonates loading methods used in these studies, and also to vastly different detection methods. The longer term cumulative release, however, was similar between these studies and our study—the drug release after one month had plateaued . Our long‐term fractional release curve [Fig…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These opposing results may be attributed to different inorganic phases and bisphosphonates loading methods used in these studies, and also to vastly different detection methods. The longer term cumulative release, however, was similar between these studies and our study—the drug release after one month had plateaued . Our long‐term fractional release curve [Fig…”
Section: Discussionsupporting
confidence: 83%
“…Fractional releases of RAC from CSC, however, were much lower compared to the previous results for CPC or other apatites, where more than 20% of alendronate was released within 3 weeks. In contrast, another study reported that the cumulative zoledronate release from commercial hydroxyapatites and CPC was in the 10 −6 M range . These opposing results may be attributed to different inorganic phases and bisphosphonates loading methods used in these studies, and also to vastly different detection methods.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…HA has been proven to have an excellent bone repair properties, for example, stimulating tissue regeneration (Sun et al, 2008;Ooms et al, 2003;Apelt et al, 2004;Lin et al, 2009;Fox et al, 2012;Sorensen et al, 2013). These properties of HA are very important because bone tissue constantly undergoes remodeling, a process whereby bone tissue is simultaneously replaced and removed by the bone cells (osteoblasts and osteoclasts, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more efforts have been focused on the possibility of combining hydroxyapatite with other drugs and materials for multipurpose applications, such as antimicrobial treatments, osteoporosis treatments and magnetic manipulation (Fox et al, 2012). HA may be loaded with active agents by adsorption offering a perspective for providing innovative drug-delivery systems (McLeod et al, 2006;Sorensen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%